14x-6=42

Simple and best practice solution for 14x-6=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14x-6=42 equation:


Simplifying
14x + -6 = 42

Reorder the terms:
-6 + 14x = 42

Solving
-6 + 14x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 14x = 42 + 6

Combine like terms: -6 + 6 = 0
0 + 14x = 42 + 6
14x = 42 + 6

Combine like terms: 42 + 6 = 48
14x = 48

Divide each side by '14'.
x = 3.428571429

Simplifying
x = 3.428571429

See similar equations:

| 3h+10=-2 | | 8q+p-9p-p= | | 5b^2+27b+28=0 | | 2.50m+4m=26 | | -3c-12-c=-8 | | 9.2x-6.4=8.2 | | 2.50m-4m=26 | | 5+2x=6-2x | | 7x+8x=45+6x | | 4y-5+4y-7= | | 26=2.50m-4m | | log(12)-log(5x^2)=log(x+3)+log(x+2) | | X-3.3(x+6.7)=-53.85 | | X-3.3(x+6.7)=-53.58 | | 18-2x+4x=-8 | | 3x-9x=37 | | u^2-36u+35=0 | | 4h+5h=15 | | a/2+a/3+a/4=26 | | 4.06=12.6(5+3.5x)-2x | | ln(12)-ln(5x^2)=ln(x+3)+ln(x+2) | | -4d+6-4=18 | | 4*6+12=2*6+30 | | -4+8x+23=3 | | -6(r-7)=90 | | 17+2.6=30 | | 1(3/4)/4(1/8)= | | 6.9+8p=-12.3 | | 3t/4-6=t/12 | | .66(m-8)=4 | | 26m=55 | | 5t+5.7=9.2 |

Equations solver categories